2011
DOI: 10.1152/ajpendo.00543.2010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influence on diabetic rat embryopathy

Abstract: Ejdesjö A, Wentzel P, Eriksson UJ. Genetic and environmental influence on diabetic rat embryopathy. Am J Physiol Endocrinol Metab 300: E454 -E467, 2011. First published November 30, 2010 doi:10.1152/ajpendo.00543.2010We assessed genetic and environmental influence on fetal outcome in diabetic rat pregnancy. Crossing normal (N) and manifestly diabetic (MD) Wistar Furth (W) and Sprague-Dawley (L) females with W or L males yielded four different fetal genotypes (WW, LL, WL, and LW) in N or MD rat pregnancies fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…In our previous work with WL and LW F 1 offspring, a combination of embryonic susceptibility and maternal milieu appeared as the most plausible explanation for differences in fetal outcome (19), a notion applicable also on the results in the present study.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In our previous work with WL and LW F 1 offspring, a combination of embryonic susceptibility and maternal milieu appeared as the most plausible explanation for differences in fetal outcome (19), a notion applicable also on the results in the present study.…”
Section: Discussionsupporting
confidence: 84%
“…As discussed above, different polymorphism in W and L mitochondria might lead to disturbed mitochondrial function in a hyperglycemic environment. The influence of parental genotype and maternal diabetes on gene expression patterns of ROS scavenging enzymes and key developmental genes are similar in the F 2 offspring in this present work compared with F 1 offspring in previous experiments (19). Furthermore, MD-WLWL offspring show a decreased mandibular gene expression of CuZnSOD, MnSOD, ECSOD, and Gpx1 compared with MD-LWLW offspring.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Outbred strains, such as ICR, appear to be susceptible to diabetes-induced neural tube defects [Oyama et al, 2009; Wu et al, 2012], with NTD incidence as high as 75% in ICR mice, although non-diabetic controls also showed a high rate of defects (24%) in one study [Phelan et al, 1997]. In the rat, genetic background also appears to modulate the susceptibility to craniofacial defects in diabetic pregnancies [Ejdesjo et al, 2011; Nordquist et al, 2012], although the molecular mechanisms underlying differential susceptibility are unknown at present. In the mouse, strain-specific differences in the position of the rostral closure site [Juriloff et al, 1991] have been suggested to influence the susceptibility to anterior neural tube defects.…”
Section: Maternal Diabetes and Neural Tube Defects In Animal Modelsmentioning
confidence: 99%